RANCANG BANGUN PENYARING AIR OTOMATIS - Mabrur, Mabrur; Iswadi, Iswadi; Said L, Muh (JFT : Jurnal Fisika dan Terapannya, 2015)
This research aims to design and design an automatic water filter and test the quality of the filtered water using an automatic filter that has been designed. The quality of the filtered water is viewed from physical and chemical parameters, both parameters are measured and observed directly at the Modern Physics Laboratory of the Faculty of Science and Technology and the Physical Chemistry Laboratory of the Faculty of Science and Technology. Based on the results of the study, it was found that the results of water quality in an automatic water filter with proof of two different samples showed that the water produced was not maximal because it had a high conductivity value and a pH value that was in the acid category. Because the water pressure that enters the filter media is too large it can stir / destroy the top layer of the filter so that the top filter cannot filter out impurities optimally.